Reaksi Investor Pada Saham Perusahaan Sub Sektor Perhotelan, Restoran Dan Pariwisata Pada Masa Pandemi Covid - Via Krismawati; Maslichah Maslichah; Dwiyani Sudaryanti (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
Covid Pandemic has multidimensional effect to economic activity. It affects investor reaction to the prospect of industrial sector in Indonesia. The objective of this study aims to study the investor reaction during Covid pandemic on the shares of hospitality industry, restaurant, and tourism subsector The population of this research is hospitality industry, restaurant, and tourism subsector on the BEI with purposive sampling as its technique. The proxy of investor reaction is Average Trading Volume Activity in monthly basis. This study compares two period of reaction, 7 months before Pandemic and 7 months during Covid Pandemc. The data were analyzed using paired t test. The results showed that there was no difference between before and during Covid Pandemic. Investors are still positive on the prospect of hospitality industry, restaurant, and tourism subsector. It implies on a need of a supportive policy from government to keep the investor’s trust, such as issuing tax amnesty for those industry.